The Effects of Service Quality Towards Consumer Responses through The Image of Private University in East Java - Panjaitan, Hotman Petrick (Institute of Advanced Engineering and Science, 2013)
Private universities should realize the appropriate quality requirements demanded by consumers. Where quality is the issue in a consistent and efficient way to deliver what is desired and expected by consumers. Consumer response is reflected in the prospective student's decision to choose private Universities that provide the best quality service in the academic field.The result of tested model from this research, was able to explained the relation between service quality on consumer responses through private University’s image in east java.With using proporsional random sampling, analysis structural equation model (SEM), and the help from Amos software, on 200 private University student samples, showed that service quality affects towards private University image’s. Private University image’s affects towards consumer response. Meanwhile service quality indirect effects towards consumer responses through private University image’s.DOI: http://dx.doi.org/10.11591/ijere.v2i2.1714